A Rare Congenital Anomaly: Surgery of Combined Discrete Subaortic Membrane Complicated by the Absence of the Superior Vena Cava (Annals of Medical Research, 2021)
None
Keywords: Superior Vena Cava; Systemic Venous Return Anomaly; Discrete Subaortic Stenosis; Cardiovascular Surgery.